Transposable elements acquire time- and sex-specific transcriptional and epigenetic signatures along mouse fetal gonad development - Stévant, Isabelle; Gonen, Nitzan; Poulat, Francis (Frontiers in Cell and Developmental Biology, 2024)
Gonadal sex determination in mice is a complex and dynamic process, crucial for the development of functional reproductive organs. The expression of genes involved in this process is regulated by a variety of genetic and epigenetic mechanisms. Recently, there has been increasing evidence that transposable elements (TEs), which are a class of mobile genetic elements, play a significant role in regulating gene expression during embryogenesis and organ development. In this study, we aimed to investigate the involvement of TEs in the regulation of gene expression during mouse embryonic gonadal development. Through bioinformatic analysis, we aimed to identify and characterize specific TEs acting as regulatory elements for sex-specific genes, as well as their potential mechanisms of regulation. We identified TE loci expressed in a time-and sex-specific manner along fetal gonad development that correlate positively and negatively with nearby gene expression, suggesting that their expression is integrated to the gonadal regulatory network. Moreover, chromatin accessibility and histone post-transcriptional modification analyses in the differentiating supporting cells revealed that TEs are acquiring sex-specific signature for promoter-, enhancer-, and silencer-like elements with some of them being proximal to critical sex determining genes. Altogether, our study introduces TEs as new potential players of the gene regulatory network controlling gonadal development in mammals.